Метод обробки радіаційними технологіями спеціального одягу для забезпечення гігієни праці - Черняк, Олена Миколаївна (НТУ "ХПІ", 2018)
У статті зазначено про важливість догляду за спеціальним одягом робітників, проведено аналіз сучасних підходів до дезінфекції та визначено певні недоліки цих методів. Запропоновано проводити стерилізацію спецодягу методом пучком прискорених електронів. Для того, щоб визначити яка доза буде ефективна для стерилізації одягу, проведено експеримент, щодо визначення бактерій та мікроорганізмів, в матеріалах спеціального одягу, до дезінфекції іонізуючим -випромінюванням та після. Визначено і обґрунтовано необхідність використання чисельного моделювання в радіаційних технологіях.

Among many means of individual protection a special place is reserved for special clothing, since it constantly contacts the body of a person, promotes the creation of a microclimate and protects against various unfavorable factors in the production environment. The purpose of this work is to conduct experimental studies to confirm the hypothesis about the possibility of applying radiation technologies for the disinfection of special clothing. The analysis of modern approaches to the disinfection of special clothing has been carried out, and certain deficiencies of these methods have been identified, for example, insulated clothing and clothing treated with special substances, washing is forbidden. It is proposed to carry out sterilization of overalls by a beam of accelerated electrons. The advantages of radiation treatment are determined - high ecological safety, low cost, and the product itself after treatment, subject to compliance with the technological regulations, is non-toxic. In order to determine which dose will be effective for the sterilization of clothing, an experiment was conducted to identify bacteria and microorganisms in special clothing materials, to disinfection with ionizing radiation and after. The advantages of numerical simulation in radiation technologies are presented in detail, which at present is one of the most powerful methods for calculating the dose map, absorbed dose, and range of charged particles. On the example of numerical simulation of gamma rays performed by GEANT4 - convergence of simulation results and dosimetric measurements was 88-90%.
The method of processing the special clothes of radiation technology to provide occupational health
Keywords: дезінфекція; радіаційні технології; іонізуюче випромінювання; поглинена доза; прискорювач електронів; чисельне моделювання; disinfection; ionizing radiation; absorbed dose; electron accelerator